2005
DOI: 10.1007/s00330-005-0019-y
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of teleradiology using Dicom e-mail: recommendations of the German Radiology Society

Abstract: Until recently there has been no standard for an interoperable and manufacturer-independent protocol for secure teleradiology connections. This was one of the main reasons for the limited use of teleradiology in Germany. Various teleradiology solutions have been developed in the past, but the vast majority have not been interoperable. Therefore an ad hoc teleradiology connection was impossible even between partners who were already equipped with teleradiology workstations. Based on the evaluation of vendor-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 10 publications
0
17
0
2
Order By: Relevance
“…In our study, it was revealed that 41.6% of the participants did not use teleradi-ology systems and we consider that the main reasons and lack of financial support and technical problems. 7,[10][11][12] It was also found that DICOM was the most commonly transmitted format (63.3%), as revealed in the European and Swiss survey. 7,10 In our study, the most common reason for the use of teleradiology outsourcing was revealed as secondary readings and expert consultation, and the most common disadvantages were revealed as insufficient integration of clinical history and lack of contact with the radiologist.…”
Section: 7-9mentioning
confidence: 85%
“…In our study, it was revealed that 41.6% of the participants did not use teleradi-ology systems and we consider that the main reasons and lack of financial support and technical problems. 7,[10][11][12] It was also found that DICOM was the most commonly transmitted format (63.3%), as revealed in the European and Swiss survey. 7,10 In our study, the most common reason for the use of teleradiology outsourcing was revealed as secondary readings and expert consultation, and the most common disadvantages were revealed as insufficient integration of clinical history and lack of contact with the radiologist.…”
Section: 7-9mentioning
confidence: 85%
“…Commercial gateways also allow the integration of these non-DICOM attachments into the DICOM workflow using a web server. DICOM images and non-DICOM attachments are joined with these solutions, as long as they are encoded using the X-tags according to the German national DICOM-e-mail standard [5,6].…”
Section: Server Based Teleradiology Gatewaymentioning
confidence: 99%
“…The DICOM-e-mail protocol is described in detail in [6]. In summary it is based on the exchange of standard e-mails with an additional encryption according to the OpenPGP standard [12,13].…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…In [2], an example of DICOM protocols' vendor-specific addition for the implementation of certain teleradiology solutions is demonstrated. Moreover, a variety of common Internet protocols, that is, HTTP, FTP, SMTP, IMAP4, POP3, as well as vendor-dependent protocols are evidently acceptable in certain teleradiology solutions [35]. …”
Section: Introductionmentioning
confidence: 99%